AN ANALYSIS OF FORMAL AND CASUAL REGISTER IN THE MOVIE “RUN” 2020 - Erlangga, Muhamad Eginda (Universitas Negeri Malang, 2023)
The objective of this research is to find the formal and casual register used by the characters in the movie “Run” 2020. This research uses the qualitative type of research and uses the descriptive approach to analyze and identify the data obtained. The data were analyzed using Martin Joos’s theory of register. Based on the result there are 10 pieces of data obtained from the movie. The data identified as 2 data (20%) is formal register and 8 data (80%) is casual register. The casual register dominates the result because in the movie there is no such circumstance that requires to use formal register. The investigation shows that field and tenor factors influence how the register is used in communication by interlocutors.